THE MUSICAL LANGUAGE OF KYRGYZ KÜÜ: EMPATHY AND MEANING (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This scientific article explores the role of music in traditional Kyrgyz culture and analyzes the perception of komuz melodies as a “musical language.” It also examines music’s influence on the human spiritual world, its function in shaping individual and collective consciousness, and its psychological, communicative, and existential aspects. In the context of modern globalization and the music industry’s powerful impact, the article discusses the significance of projects essential for the preservation, development, and international promotion of Kyrgyz traditional musical art, including the “Rukh Sanat” World Festival.
Keywords: Kyrgyz traditional music, komuz, kyl kyyak, musical language, ethnomusic, authentic performance, existential meaning, “Rukh Sanat” festival, cultural heritage, globalization, nomadic civilization, oral professional musical art.